CLINICAL AND RADIOGRAPHIC ESTIMATION OF THE NUMBER OF ROOT CANALS IN MAXILLARY SECOND PREMOLARS AMONG A GROUP OF NORTH JORDANIAN DENTAL PATIENTS - Mashoor A. Alwreikat; Mohammad Albataineh; Ali S. Alremawi; Alaa H. Khuluqi; Musab A. Alarabeyat (Pakistan Oral & Dental Journal, 2021)
The purpose of this study was to determine the variations of root canal morphology and to evaluate the percentage of maxillary second premolar teeth that have two canals from orifice to apical foramen among a sample of north Jordanian population in routine endodontic practice. A total of 148 north Jordanian patients, 89 females and 59 males, referred to the conservative clinics in Prince Rashid hospital for root canal treatment of 2nd maxillary premolars from June 2018 to January 2019 formed the study group. They were examined clinically and radiographically by two specialists. The results of the study revealed that of the 148 second maxillary premolars teeth treated, there were 84 teeth with two canals from orifice to foramen. Fiftyone were females and 33 males. Only one patient had three canals. It was concluded that most of the maxillary 2nd premolars had two canals so endodontist must pay attention to these variations.